Implementasi PERMENDAGRI Nomor 20 Tahun 2018 Di Desa Bluri Kecamatan Solokuro Kabupaten Lamongan - Nur Karisma Dewi; Maulidah Narastri (International Forum of Researchers and Lecturers, 2024)
This research examines village financial management in Bluri Village based on Minister of Home Affairs Regulation Number 20 of 2018 in Bluri Village, Solokuro District, Lamongan Regency. The aim of this research is to determine the implementation of village financial management. This research method uses descriptive qualitative, the researcher uses a case study approach in Bluri Village, where the research informants are village officials. Observation, interviews, and document study are the data collection methods used in this research. Data analysis includes data organization, which is done by organizing the data that has been collected during the research so that it is neater. The conclusion of this research is that the implementation of village financial management in Bluri Village is broadly in accordance with Minister of Home Affairs Regulation Number 20 of 2018 starting from the planning, implementation, administration, reporting and accountability processes, although there are several things that are still not in accordance with the target time.